Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1177/026010600601800309
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid in Neural Signaling Systems

Abstract: Docosahexaenoic acid has been conserved in neural signalling systems in the cephalopods, fish, amphibian, reptiles, birds, mammals, primates and humans. This extreme conservation, despite wide genomic changes over 500 million years, testifies to a uniqueness of this molecule in the brain. The brain selectively incorporates docosahexaenoic acid and its rate of incorporation into the developing brain has been shown to be greater than ten times more efficient than its synthesis from the omega 3 fatty acids of lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 50 publications
3
24
0
1
Order By: Relevance
“…In the current study, exercise and DHA increased alpha and beta activities. Similarly, in previous studies it was shown that exercise (Youngstedt et al, 1993) and DHA (Crawford 2006;Takeuchi et al, 2002) increased alpha and beta activities. While an increase in alpha activity is related to alertness (Nerad and Bilkey, 2005), vigilance (Olbrich et al, 2009), and semantic memory in humans (Klimesch, 1999), increase in beta activity is related to alertness (Nerad and Bilkey, 2005), attention (Makeig and Jung, 1995), emotion (Cole and Ray, 1985), anger (Rusalova et al, 2003), and sensorimotor cortex (Parkes et al, 2005) activities.…”
Section: Exercise and Dha Effects In Hypoxiasupporting
confidence: 75%
See 2 more Smart Citations
“…In the current study, exercise and DHA increased alpha and beta activities. Similarly, in previous studies it was shown that exercise (Youngstedt et al, 1993) and DHA (Crawford 2006;Takeuchi et al, 2002) increased alpha and beta activities. While an increase in alpha activity is related to alertness (Nerad and Bilkey, 2005), vigilance (Olbrich et al, 2009), and semantic memory in humans (Klimesch, 1999), increase in beta activity is related to alertness (Nerad and Bilkey, 2005), attention (Makeig and Jung, 1995), emotion (Cole and Ray, 1985), anger (Rusalova et al, 2003), and sensorimotor cortex (Parkes et al, 2005) activities.…”
Section: Exercise and Dha Effects In Hypoxiasupporting
confidence: 75%
“…Similarly, previous studies reported that exercise (Li et al, 2008;Youngstedt et al, 1993) and DHA (Crawford, 2006;Takeuchi et al, 2002) decreased delta activity. Also, in our results, delta activity was found to be high in all groups.…”
Section: Eeg Wavessupporting
confidence: 68%
See 1 more Smart Citation
“…ω3 deprivation reduces the blood DHA levels by 89% and the brain DHA levels by 37% 44) . EPA to DHA conversion may be restricted in order to maintain constant DHA levels for nervous system signaling 45) . Although the reason for this phenomenon is unknown, the following may be a potential cause.…”
Section: Subclasses Of Platelet Phospholipidsmentioning
confidence: 99%
“…DHA serves not only as a building block for neural development, but also as a functional molecule to maintain proper fluidity of neuronal membranes and modulate neurochemical, gene expression, and memory processes (2). Clinical evidence indicates that term infants given formula supplemented with either DHA plus arachidonic acid or DHA alone have substantially better visual acuity (3) and improved cognitive ability (4).…”
mentioning
confidence: 99%